Bacteria vs. Bacteriophages: Parallel Evolution of Immune Arsenals - Shabbir, Muhammad A. B.; Hao, Haihong; Shabbir, Muhammad Z.; Wu, Qin; Sattar, Adeel; Yuan, Zonghui (Frontiers in Microbiology, 2016)
Bacteriophages are the most common entities on earth and represent a constant challenge to bacterial populations. To fend off bacteriophage infection, bacteria evolved immune systems to avert phage adsorption and block invader DNA entry. They developed restriction-modification systems and mechanisms to abort infection and interfere with virion assembly, as well as newly recognized clustered regularly interspaced short palindromic repeats (CRISPR). In response to bacterial immune systems, bacteriophages synchronously evolved resistance mechanisms, such as the anti-CRISPR systems to counterattack bacterial CRISPR-cas systems, in a continuing evolutionary arms race between virus and host. In turn, it is fundamental to the survival of the bacterial cell to evolve a system to combat bacteriophage immune strategies.